Analisis Dampak Kunjungan Damkar terhadap Peningkatan Pengetahuan dan Keterampilan Mitigasi Bencana Kebakaran di SDN 2 Donosari Kecamatan Patebon Kabupaten Kendal - Derana Abidatul Beridanissa; Anni Qorinatul Ula; Dhini Wahyu Ningtyas; Bagas Adi Pramana; Tri Setiawan; Waulaida Tsania Salma; Zulfia Ludfiani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the impact of the Fire Department’s (Damkar) visit on enhancing knowledge and skills in fire disaster mitigation among students and teachers at SDN 2 Donosari, Patebon District, Kendal Regency. The background of this research is the low level of awareness and preparedness in the community, especially elementary school children, in dealing with fire hazards. A qualitative approach with a descriptive method was employed. Data were obtained through in-depth interviews with firefighters, teachers, and students, then analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The results revealed that socialization and simulation activities conducted by firefighters improved students’ understanding of fire hazards, self-rescue strategies, and the use of fire extinguishing equipment. Hands-on experiences such as evacuation drills and fire extinguishing practices provided meaningful contextual learning and encouraged early risk awareness. The strategic role of firefighters in establishing friendly and interactive communication was proven effective in increasing students’ enthusiasm and engagement. This study emphasizes the importance of disaster education at the elementary school level as a preventive effort to minimize risks and impacts of fire disasters within the community.